(3cJGH GdHQgGf aj JQJjH ShQ GdbQBfs - (3CMeO Hf EHQGgje Hf GdRHjQ GdKbaj GdZQfGWj, CHh LYaQ,J (B708 (3g` s ((3jhSa Hf Gdhcjd GdHdhi s)
(3ChdgG (B:s
(3GdMeO ddg GdMcje GdYdje GdYdi GdYXje hHYO aEfi EYJHQJ bhdg Udi Gddg Ydjg hSde (B:" (3eG ef fHi EdG hbO ChJi ef GdGjGJ eG eKdg Gef Ydjg GdHTQ hEfeG cGf GdPi ChJjJ aCQLhG Cf Cchf GcKQge JGHYkG jhe GdbjGeI s
(3BNQgG (B:s
(3ShQI GdfGS hLg JCNQgG Yf TbjJgG Yehe GdChdi hNUhU GdKGfjI hbO Je GdYQV eeG bUOfGg hdG LgGdg HGdbOQ hGdMeO ddg s
(3Hg ChQGb UaQGAs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B86s
Keywords: (3GdJaSjQ hYdhe GdbQBfs